CONSTRUCTION OF A GOODS ELEVATOR WITH A MANUAL PULLEY SYSTEM - Yanel, Karnova (Jurnal Teknologi dan Vokasi, 2025)
An elevator, commonly referred to as a lift, is a lifting device frequently used in multi-story buildings to transport people or goods. In the context of this design, the objective is to develop an elevator for a two-story building with a height of 4 meters. The background of this project is to provide a practical and efficient elevator system for buildings that do not require high-capacity or complex machinery. The purpose of this design is to create an affordable and reliable manual pulley-based elevator system suitable for low-rise buildings. The methodology includes observation of existing elevator systems, the application of established design standards, and a thorough literature review. Based on these inputs, the elevator utilizes a manual pulley system with a maximum load capacity of 540 kg. The cabin, which accommodates four people, is lifted using six ropes of type 8x19 with a diameter of 13 mm. The cabin is guided by T90 rails and is equipped with a wedge-type safety gear system for enhanced security. The results of the design show that the system meets the required specifications for load capacity and safety, while remaining cost-effective and efficient for the intended application. In conclusion, this manual pulley elevator system is a feasible and practical solution for small to medium-sized buildings, offering both reliability and safety within a modest budget